Mechanical Behaviors and AE Characteristics of Brittle Coal Specimens with Different Fissure Angles - Xuebin Gu; Weiyao Guo; Chengguo Zhang; Chuanqing Guo; Chao Wang; Fangfang Wang; Tongbin Zhao; Yang Chen (Geofluids)
Uniaxial compression tests were performed on coal specimens with five fissure angles to study the mechanical behaviors and acoustic emission (AE) characteristics of fractured coals. AE and video monitoring techniques were used to examine crack propagation in the fractured specimens. The stress–strain curves, mechanical properties, and cracking processes at different fissure angles were analysed. The AE counts and dominant frequency characteristics, during the failure processes of the specimens, were investigated. In addition, five types of AE signals were classified according to the AE spectral frequency analysis, and low-frequency–high-energy signals were used to accurately predict the brittle fracture processes of the fractured specimens. Finally, a comparison with sandstone specimens revealed the influence of primary cracks on the strength of brittle coal specimens containing preexisting fissures under uniaxial compression. The test results are helpful to elucidate the mechanical behavior and failure mechanism in underground engineering, such as hydraulic slotting in mines.